Skyrmion dynamics in magnetic thin films - Gan, Weiliang (Nanyang Technological University, 2020)
Magnetic skyrmions are nanoscopic magnetization textures that have intrigued the spintronics community for more than a decade now due to their potential as a next-generation information carrier. Their highly sought-after characteristics, such as high current-induced transport speeds, small sizes, and topological stability allows them to simultaneously fulfil the function of both random-access memory and high capacity storage media. However, several challenges should first be addressed, such as the skyrmion Hall effect (SkHE), skyrmion transport efficiency, and the lack of suitable injection methods. In this thesis, the dynamics of skyrmions under the influence of spin-orbit torques and magnetostatic field gradients were investigated by using a combination of theoretical and numerical modelling methods. Our model on spin-orbit torque reveals that the skyrmion speed scales linearly with its size, leading to a tradeoff between skyrmion density and speed. A mechanism exploiting the transverse repulsive forces from the nanowire edges was revealed, where the skyrmion speed was shown to be increased many times. A similar mechanism was found in antiferromagnetically-coupled skyrmions, that allows the negation of the SkHE while passively increasing their speed. Furthermore, the difficulty in nucleating these type skyrmions was also tackled; a combination of DMI-induced edge tilting and spin-orbit torque allows single skyrmions to be injected on-demand efficiently. For the development of energy-efficient skyrmion memory devices, a model was developed to describe the skyrmion motion under a voltage-controlled magnetic anisotropy (VCMA) gradient. As no electric currents are required, the VCMA-based devices consume several orders of magnitude lesser power. A VCMA-based device architecture was proposed using multiplexed discrete gate electrodes. A maximum speed of 70 ms-1 was achieved, similar to current-induced speeds. However, VCMA-based devices are clear winners in terms of design flexibility; a recirculating skyrmion track was demonstrated, where skyrmions could be shifted and cycled in a loop. To overcome the SkHE in such devices, a transverse driving scheme was devised such that the net skyrmion motion is directed parallel to the device axis. Finally, a hybrid drive combining both the transverse and longitudinal scheme was also demonstrated, resulting in high velocity skyrmion motion with low SkHE. While only a few types of skyrmion devices were discussed, the model developed in this thesis serves as a platform for the design of novel VMCA devices.